(untitled) (Revista Contexto & Educação, 2021)
Yellow fever is a serious disease, effectively prevented by vaccination. Between 2017 and 2018, Brazil had a considerable increase in the number of cases of wild yellow fever and deaths resulting therefrom, especially in areas that were not considered at risk. In opposition to fake news that stimulate non-vaccination, our proposal was to use a meme with the image of Oswaldo Cruz, as a trigger, in Biology classes of a Technical Course in Telecommunications Integrated to High School of a public institution, in Petrópolis (RJ), of discussions about yellow fever and its prophylaxis, leading to 100% of vaccination coverage among these students. Public health issues, such as this one, can and should be taken into the classroom, not only in Biology, but in a multidisciplinary way, promoting debates and contributing to a scientific dissemination movement, as well as for the prophylaxis of this and other diseases.